The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/dth.12841
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of Hidradenitis suppurativa and botulinum toxin type a therapy: A novel approach for a pathology that is still difficult to manage

Abstract: Hidradenitis suppurativa is a chronic skin disease with an intense inflammatory activation. It typically affects the intertriginous areas with cysts, fistulae, and scarring extremely painful. Patients suffer from severe psychological impact. HS still results in a high unmet medical need with several underdiagnosed cases, probably due to the incomplete knowledge of the pathogenesis of HS. The use of botulinum toxin a has recently been proposed as an effective therapy for HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…Additionally, total lesions were reduced in the active group at 3 and 6 months, respectively, as well as after BTX-B in an open setting in the former placebo group. Our pilot study confirms previous case reports [ 14 17 ] with a positive outcome of BTX treatment in HS and encourages further interventional studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, total lesions were reduced in the active group at 3 and 6 months, respectively, as well as after BTX-B in an open setting in the former placebo group. Our pilot study confirms previous case reports [ 14 17 ] with a positive outcome of BTX treatment in HS and encourages further interventional studies.…”
Section: Discussionsupporting
confidence: 90%
“…Five patients have previously received BTX-A injections for HS, with a positive outcome [14][15][16][17], whereas a study performed in five HS patients reported improvement in the Dermatology Life Quality Index (DLQI), but not for the number of nodules or VAS for pain [18].…”
Section: Introductionmentioning
confidence: 99%
“…Given the apocrine distribution of HS, we hypothesized that hyperhidrosis could be a comorbidity that contributes to disease activity and morbidity. This hypothesis was supported by 5 case reports [1][2][3][4][5] demonstrating the excellent response of HS in 6 patients (of whom 3 demonstrated clinical remission) who were treated with botulinum toxin A (BoNT-A), a treatment for hyperhidrosis approved by the U.S. Food and Drug Administration. Half of these patients presented with hyperhidrosis or increased sweat production.…”
Section: Hyperhidrosis Affects Quality Of Life In Hidradenitis Suppurmentioning
confidence: 86%
“…We therefore sought to confirm the efficacious treatment of HS by BoNT-A, as demonstrated by the 5 case reports. [1][2][3][4][5] To investigate this, we conducted a prospective analysis to assess the effectiveness of one-time treatment of BoNT-A (100 units, 2.5 units per 1.5 cm) in 5 patients with HS at the Stanford Department of Dermatology. All patients were female and endorsed excessive sweating, with an average age of 38.6 years and Hurley stages I to III.…”
Section: Hyperhidrosis Affects Quality Of Life In Hidradenitis Suppurmentioning
confidence: 99%
“…She received an injection every 3 months (four times thus far), which had significantly helped alleviate her pain and curbed the progress of her HS by resolving abscesses and healing draining sinuses. Campanati et al [155] investigated the potential therapeutic role of BoNT-A in HS by treating 2 patients. The first patient, a 23-year-old woman, suffering from axilliary HS, was treated with 50 U of BoNT-A per axilla while the second patient, a man of 50 -year-old with a HS of the groin and inner thighs, was treated with 100 U of BoNT-A for each side.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%